Incorporating changeable attitudes toward vaccination into compartment models for infectious diseases - Jiang, Yi; Kurianski, Kristin; Lee, Jane; Ma, Yanping; Cicala, Daniel; Ledder, Glenn (Mathematical Biosciences & Engineering, 2025)
We develop a mechanistic model that classifies individuals both in terms of epidemiological status (SIR) and vaccination attitude (Willing or Unwilling/Unable), with the goal of discovering how disease spread is influenced by changing opinions about vaccination. Analysis of the model identifies the existence and stability criteria for both disease-free and endemic disease equilibria. The analytical results, supported by numerical simulations, show that attitude changes induced by disease prevalence can destabilize endemic disease equilibria, resulting in limit cycles.
Keywords: Computer science; Disease; Econometrics; Endemic disease; Environmental health; Epidemic model; Epidemiology; Immunology; Infectious disease (medical specialty); Limit (mathematics); Machine learning; Mathematics; Medicine; Pathology; Stability (learning theory); Vaccination; dept.mat